The Emergence of Political Opposition in Mexico, 1949-1952. Two Proposals for Electoral - Ayala López, José Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Using methodological elements from political and institutional history, the present article analyzes, the first proposal for the implementation of an electoral system of proportional representation in Mexico and its primary repercussions in the formulation of subsequent electoral laws. This initiative was presented by Vicente Lombardo Toledano and the Popular Party (PP) in 1951, during the XLI Legislature (1949-1952). This event is correlated with the emergence of political opposition in the Chamber of Deputies. In the same year as the PP proposes reform, the National Action Party (PAN) proposes another initiative of electoral reform. Both proposals propitiate a legislative debate that identifies the importance of elections as an instrument of State political control and proposed its reformulation. In this sense, the principal contribution of this study is to visibilize the proreform discourses of political opposition in a period which is often through of as being characterized by authoritarianism and censorship.